2017
DOI: 10.18821/1728-2802-2017-21-6-337-339
|View full text |Cite
|
Sign up to set email alerts
|

Oral Hygiene and Dental Health of First Moscow State Medical University Students

Abstract: In the prevention oforal diseases, dental hygienic status, proper oral hygiene, the proper choice ofmeans and methodsfor performing hygienic dental activities are essential. However, even among future doctors, the hygienic state of the oral cavity leaves much to be desired. Basic knowledge of oral hygiene and the principles ofprevention ofdental diseases are necessary for physicians of various specialties, since there is often a relationship between dental diseases and diseases of other organs and systems of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…DAI index values <25 were determined in 68% of the examined, DAI values equal to 26-30 -in 16% of young people, DAI values equal to 31-35 -in 11%. Values of the DAI index >36, indicating the presence of very severe disorders and an unconditional need for treatment, were found in 5% of the examined [30].…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…DAI index values <25 were determined in 68% of the examined, DAI values equal to 26-30 -in 16% of young people, DAI values equal to 31-35 -in 11%. Values of the DAI index >36, indicating the presence of very severe disorders and an unconditional need for treatment, were found in 5% of the examined [30].…”
mentioning
confidence: 93%
“…Makeeva I.M. and co-authors identified maxillofacial deformities in 69.3% of Moscow students aged of 16 to 2-year-olds and of 21 to 25-year-olds [31].…”
mentioning
confidence: 99%